Corporate weakness of will - Silver, Kenneth (Journal of business ethics, 2025)
Proponents of corporate moral responsibility take certain corporations to be capable of being responsible in ways that do not reduce to the responsibility of their members. If correct, one follow-up question concerns what leads corporations to fail to meet their obligations. We often fail morally when we know what we should do and yet fail to do it, perhaps out of incontinence, akrasia, or weakness of will. However, this kind of failure is much less discussed in the corporate case. And, where it is discussed, the view is that corporations are less prone to weakness. Here, I argue that proponents of corporate responsibility should say that corporations can and often do instantiate weakness of the will, and that this is important to recognize. Weakness of the will requires certain capacities that these proponents typically take corporations to have. And once this is appreciated, we can assess how corporate weakness might proceed differently than how it does for individuals. We can also begin a conversation about how best to meet the distinctive challenges for recognizing and correcting corporate weakness, using a number of resources from management scholarship.